Characteristics of Active Carbon from Utilization of Red Chili Trees (Capsicum annuum L) - Ni Made Dwidiani; Putu Wijaya Sunu; Gusti Ngurah Nitya Santhiarsa (EPI International Journal of Engineering, 2019)
This work studies the use of red chilli tree (capsicum anuumm L) waste as material of activated carbon and examines the morphological structure and elemental composition of the activated chili trees. The morphological structure was measured at TekMIRA (Pusat Penelitian dan Pengembangan Teknologi Mineral dan Batubara, Bandung) by using the scanning electron microscope (SEM), and the composition of the elements of carbon, hydrogen, nitrogen and ash is determined by the ultimate testing analysis with the ASTM D5373 standard. In the testing procedure, activated carbon is made from red chili tree waste by dehydration with a temperature of 2000 C for 1 hour and carbonized with a temperature of 3750 C for 1 hour. Then, the chemical activation (NaOH) is made in variation of concentration of 1%, 3%, and 5% with soaked time 24 hours, and dried at 2000 C for one hour. The carbonization at a concentration of 1% (NaOH) gave the best result on activated carbon from red chili trees.